The duty to bring terrorists to justice and discretionary prosecution: hStefano Betti - Betti, Stefano (Journal of international criminal justice, 2010)
In Res. 1373 (2001), the Security Council laid down the duty to bring terrorists to justice and to deny them safe haven. Whereas such duty expressed a clear political imperative in the aftermath of 11 September 2001, it is less clear how national authorities are supposed to translate it into a set of enforceable legal obligations. If it is interpreted as obliging states to prosecute and try terrorists, as the Security Council Counter Terrorism Committee seems to suggest, the power of prosecutors to decide whether or not to bring a case to court may be severely impaired. An unconditional obligation to bring terrorists to court would not necessarily strengthen states judicial response to the threat of international terrorism. A sensible exercise of prosecutorial discretion may be instrumental in articulating a flexible and more effective response in various circumstances. Moreover, a rigid interpretation of the requirement to bring terrorists to justice does not find support in Security Council and General Assembly resolutions on terrorism. Far from mandating that alleged offenders be unconditionally brought to trial, the universal counter-terrorism conventions and protocols limit themselves to requiring that the jurisdiction of national courts be established, which is conceptually different from imposing its actual exercise